Sites of mediation : connected histories of places, processes, and objects in Europe and beyond, 1450-1650 - Burghartz, Susanna, 1956-; Burkart, Lucas; Göttler, Christine (Intersections (Boston, Mass.), 2016)
"This book explores the dynamic relationships between sites, people, objects, and images during the first age of globalization in early modern Europe. It investigates interactions, interconnections and entanglements on both micro and macro levels, and aims to understand the specific dynamics of processes of translocal and transcultural intersection. Linking global history with the history of material culture, Sites of Mediation highlights the potential of objects, artefacts, and things to connect (urban) cultures and imaginaries. Individual chapters focus on a number of European cities, which all operated on different levels of global and interregional connections and are presented here as sites of connectivity, encounters, and exchange. Contributors are: Tina Asmussen, Nadia S. Baadj, Benedikt Bego-Ghina, Davina Benkert, Daniela Bleichmar, Franziska Hilfiker, Nicolai Kölmel, Ivo Raband, Jennifer Rabe, Antonella Romano, Michael Schaffner, Sarah-Maria Schober, Claudia Swan, and Stefanie Wyssenbach"--Provided by publisher.